The market reaction to international cross-listings: evidence from Depositary Receipts - Miller, D (Journal of Financial Economics, 1999)
This paper examines the stock price impact of international dual listings. The sample consists of 181 firms from 35 countries that instituted their first Depositary Receipt program over the period 1985–1995. The market reaction to a Depositary Receipt program is larger in magnitude and more pervasive than previously reported. The stock price reaction is related to choice of exchange, geographical location (i.e., emerging or developed markets), and avenues for raising equity capital (i.e., public versus private offerings).